Safety and long-term efficacy of autologous hematopoietic cell transplantation for patients with systemic sclerosis - Eleni Gavriilaki; Eleni Gavriilaki; Despina Mallouri; Ioannis Batsis; Zoi Bousiou; Anna Vardi; Nikolaos Spyridis; Georgios Karavalakis; Alkistis kyra Panteliadou; Panagiotis Dolgyras; Christos Varelas; Vlasios I. Alevizopoulos; et al. (Frontiers in Medicine)
Autologous hematopoietic cell transplantation (HCT) has been introduced for patients with severe systemic sclerosis (SSc). We aimed to assess the safety and long-term efficacy of HCT modality for severe SSc, refractory to conventional therapy, in 17 patients who were referred to our – The Joint Accreditation Committee of the International Society for Cellular Therapy (ISCT) and the European Group for Blood and Marrow Transplantation (EBMT)-accredited Unit from 2005 to 2024. Peripheral blood stem cells were collected using cyclophosphamide and GCSF. An immunoablative conditioning regimen of cyclophosphamide and anti-thymocyte globulin was administered. Disease assessments were done before and after mobilization treatment and post-transplant, focusing on skin sclerosis, pulmonary function, cardiac involvement, gastrointestinal manifestations, the necessity for additional immunosuppressive therapy, and overall patient well-being. Before transplantation, 13/17 (76%) of the patients had diffuse skin involvement with a mean mRSS of 31 (2–49), 2/17 (12%) had pulmonary hypertension, and 14/17 (82%) had gastrointestinal manifestations. The median follow-up period was 9.1 (0. 5–14. 3) years. Improvement of skin sclerosis was observed, with a decrease in mRSS before transplantation from 31 (2–49) to 7 (2–22) post-HCT. Lung function remained stable in 8/15 (53%) patients, improved in 5/15 (33%), and deteriorated in 2/15 (13%). Gastrointestinal manifestations were improved in 12/14 (86%) patients, while all patients (16/16, 100%) reported a great impact on their quality of life. Ten out of the 16 (63%) patients were free of immunosuppressive drugs after the HCT. Overall survival was 16/17 (94.2%). Concerning TRM, there was one (1/17, 5.8%) death early post-transplant. In this specific cohort of selected patients with severe SSc refractory to immunosuppressive medications, autologous HCT led to improvements in the outcomes assessed.